2002
DOI: 10.1093/ps/81.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial function with feed efficiency within a single genetic line of male broilers

Abstract: Studies were conducted to determine relationships between feed efficiency and mitochondrial function and biochemistry. After feed efficiency (FE; gain:feed) was determined in broiler breeder males between 6 and 7 wk of age, mitochondria were isolated from breast and leg muscle from birds with high FE (0.83+/-0.01, n = 6) and low FE (0.64+/-0.01, n = 7). Respiratory chain coupling, assessed by the respiratory control ratio (RCR), was greater in high FE breast, and leg mitochondria provided NADH-linked, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
122
4
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 39 publications
22
122
4
2
Order By: Relevance
“…The association between oxidative phosphorylation and animal performance found in our study is consistent with studies that compared the performances of beef cattle (Archer et al, 1999;CastroBulle et al, 2007) and poultry (Bottje et al 2002;Bottje and Carstens, 2009) with mitochondrial function. For instance, Bottje et al (2002) suggested that the differences in performance of genetically similar animals might be partially due to mitochondrial inefficiency, as the mitochondria are responsible for 90% of the cellular production of ATP.…”
Section: Discussionsupporting
confidence: 92%
“…The association between oxidative phosphorylation and animal performance found in our study is consistent with studies that compared the performances of beef cattle (Archer et al, 1999;CastroBulle et al, 2007) and poultry (Bottje et al 2002;Bottje and Carstens, 2009) with mitochondrial function. For instance, Bottje et al (2002) suggested that the differences in performance of genetically similar animals might be partially due to mitochondrial inefficiency, as the mitochondria are responsible for 90% of the cellular production of ATP.…”
Section: Discussionsupporting
confidence: 92%
“…Breast muscle mitochondria as well as gut, leg, heart, liver, and lymphocyte homogenates from low FE birds consistently exhibit a greater pervasive total protein carbonyl content compared with high FE birds (Bottje and Carstens, 2009). This supports previous observations of greater mitochondrial ROS production in low FE broilers (Bottje et al, 2002;Iqbal et al, 2004;OjanoDirain et al, 2005OjanoDirain et al, , 2007Lassiter et al, 2006) and in our high RFI pig lines (Grubbs et al, 2013a). This is further supported by low FE steers having greater neck muscle mitochondria protein carbonyl content (Sandelin, 2005).…”
Section: Methodssupporting
confidence: 91%
“…Mitochondrial reactive oxygen species (RoS) production is closely associated with feed efficiency in pigs (Grubbs et al, 2013a) and poultry (Bottje et al, 2002). However, the cause of these differences has eluded researchers.…”
Section: Discussionmentioning
confidence: 99%